Vase life consequences of natural and chemical treatments in foxtail lily (Eremurus spectabilis), as a specialty cut flowers - Yeganeh Basiri; Nematollah Etemadi; Mahdi Alizadeh; Ali Nikbakht; Ghodratollah Saeidi (Ornamental Horticulture, 2021)
Eremurus spectabilis is a new, commercially valuable specialty cut flower, but little is known about the applicable treatments to extend the vase-life and maintaining the ornamental quality of this flower. Therefore, the present study was aimed at investigating the impacts of nano-silver, essential oils, and chemical treatments on keeping ornamental quality and vase-life of cut inflorescences of Foxtail lily. The cut inflorescences were placed in different vase solutions containing salicylic acid (100 and 200 mg L-1), methyl jasmonate (25 and 50 mg L-1), silver thiosulfate (0.1 mM) plus isothiazolinone (0.001 and 0.005 ml L-1), nano-silver (5, 10, and 15 mg L-1), thymol (75 and 120 mg L-1), and menthol (75 and 120 mg L-1), which were applied as continuous and pulsing methods. According to the results, all treatments considerably improved the post-harvest performance of Foxtail lily cut flowers. Although there were no significant differences among nano-silver (NS) treatments, the cut inflorescences kept in vase solution containing 10 mg L-1 of NS exhibited the longest vase life (~14 days) and the best ornamental quality. Nano-silver treatment followed by silver-thiosulfate significantly improved solution uptake by flowering inflorescences, thereby delaying the water balance loss and keeping relative fresh weight. Furthermore, 50 mg L-1 methyl jasmonate- and 75 mg L-1 menthol-treated cut inflorescences exhibited significantly higher vase-life longevity by ~ 6 and 4 days, total soluble solutes by 28.38% and 19.12%, and solution uptake rate by 76.46% and 140.6%, respectively, as compared to control. Overall, 10 mg L-1 NS can be recommended as a commercial preservative solution to delay flower senescence and improve the vase life and keeping the quality of foxtail cut inflorescence.